Optimizing Sharia Finance with Big Data to Overcome the Challenges of Digitalization - Dwi Indriani Fidiastutik Wijaya; Candra Pramula Pinandita; Rahma Rina Wijayanti (Al-Mashrof: Islamic Banking and Finance, 2025)
This study aims to develop a conceptual understanding of how big data can be optimized to support innovation and improve transparency, accuracy, and sharia compliance in Islamic financial institutions. A qualitative approach was employed through a systematic literature review of peer-reviewed publications from 2015 to 2025. Sources were selected based on relevance, credibility, and their contribution to understanding the nexus between big data and sharia-compliant financial systems. The findings indicate that big data enables real-time compliance monitoring, improves the accuracy of financial reporting, and enhances risk prediction aligned with Islamic jurisprudence. However, significant barriers remain, including limited technological infrastructure, privacy concerns, and the need for ethical frameworks tailored to sharia law. With targeted regulatory adjustments, infrastructure development, and capacity-building, big data holds transformative potential for the sharia finance industry. This study contributes a novel conceptual framework for data-driven transformation in Islamic finance and provides actionable insights for policymakers, regulators, and industry stakeholders seeking to align technological innovation with Islamic ethical and legal standards. Keywords: Big Data, Sharia Finance, Digital Transformation, Compliance, Financial Technology